Physical, Rheological, And Microsurface Characteristics of High-Viscosity Binder Modified with WMA Agents. (30th March 2022) - Luo, Junhui; Yang, Yuzhu; Huang, Weirong; Xie, Cheng; Chen, Jiangcai; Liu, Haobin; Ren, Tianzeng; Huang, Xiaofeng
Abstract : In order to investigate the feasibility of warm mix technology in high-viscosity asphalt mixes, in the current experiment, Shell 70 Grade A asphalt (base asphalt) was modified by AR-HVA (a high-viscosity modifier), and the high-viscosity modified asphalt was further incorporated with two surface-active warm mixes (Evotherm M1 and Retherm). The physical properties of the high-viscosity warm mix-modified asphalts were analyzed by dynamic and Brinell viscosity tests. The compatibility of the warm mixes with the high-viscosity modified and the base asphalt was analyzed by fluorescence microscopy. The modification mechanism of the high-viscosity warm mix-modified asphalts was revealed by Fourier-transform infrared spectroscopy. The high-viscosity modifier significantly reduced the penetration of the matrix asphalt and increased its softening point and 5°C ductility, whereas the two warm mixes increased the penetration and ductility of the high-viscosity modified asphalt and reduced its softening point. The surface-active warm mixes reduced the 60°C viscosity of the asphalt, and the viscosity reduction effect of M1 was better than that of Retherm. The high-viscosity modifier AR-HVA was well dispersed in the asphalt; however, its continuity was not good. The addition of the surface-active warm mixes effectively enhanced the continuity of the high-viscosity AR-HVA-modified asphalt. Infrared spectroscopy revealed little difference between the main components of the matrix asphalt and the high-viscosity asphalt. The addition of the surface-active warm mixes altered the amounts of four components in bitumen and increased its aromatic content.